2014
DOI: 10.7863/ultra.33.6.1049
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of B‐Mode Sonography of the Abdominal Muscles in Healthy Adolescents in Different Body Positions

Abstract: Sonography for assessment of the internal oblique and transversus abdominis muscles in different body positions in healthy adolescents aged 10 to 15 years was found to have reliability. To obtain high measurement reliability for the transversus abdominis and internal oblique at rest, at least 2 measurements should be performed, regardless of age, sex, or resting body position. Performing 3 measurements of the external oblique guarantees satisfactory reliability only in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…Using ultrasound for the measurement of the abdominal muscles thickness is a valid and reliable method in adolescent populations (20,21). Also previous studies on healthy subjects have shown the correlation between the body weight and the ultrasound measurements of the lateral abdominal muscles (22,30,31).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Using ultrasound for the measurement of the abdominal muscles thickness is a valid and reliable method in adolescent populations (20,21). Also previous studies on healthy subjects have shown the correlation between the body weight and the ultrasound measurements of the lateral abdominal muscles (22,30,31).…”
Section: Discussionmentioning
confidence: 95%
“…Using ultrasound for the measurement of abdominal muscles thickness and thickness changes is a valid and reliable method in adolescent population (20,21). In the only ultrasound study assessing the thickness of lateral abdominal muscles in adolescents with AIS the thickness of all three muscles (External Oblique -EO, Internal Oblique -IO and Transverse Abdominis -TrA) on both sides at rest were smaller in the AIS group compared to the control group (13).…”
Section: Introductionmentioning
confidence: 99%
“…During the ultrasound imaging procedure, the knees of the examined individuals were extended and the upper limbs placed along the sides of the trunk [12][13][14]17]. The thicknesses of the muscles were recorded at the end of normal expiration.…”
Section: Ultrasound Scanning Proceduresmentioning
confidence: 99%
“…All of them have been widely examined by ultrasound imaging, which is a relatively simple and cost-effective tool allowing reliable assessment of the muscles in different populations [12,15,28]. Some studies have tried to find some connection between OE, OI, and TrA morphology and conditions, such as low back pain and scoliosis [3,5,11,16,25].…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitative ultrasound imaging (RUSI), which allows the visualization of muscle contraction, has been shown to reliably assess the abdominal muscles in various body positions [11]. Measurement of abdominal muscle contraction thickness with RUSI during automatic response is a reliable technique in participants both with and without LBP [12].…”
Section: Introductionmentioning
confidence: 99%